Is assessing trunk muscle endurance in military with sub-acute and chronic low back pain clinically meaningful? - Pairot de Fontenay, Benoit; Perron, Marc; Gendron, Chantale; Langevin, Pierre; Roy, Jean-Sébastien (Frontiers in Sports and Active Living, 2023)
Introduction: Trunk muscle endurance (TME) tests are commonly used by clinicians to assess muscle performance changes in response to rehabilitation in patients with low back pain (LBP). The aim of this study was to assess the responsiveness of three TME-tests in patients with LBP and to evaluate the relationships between changes in TME and improvement in self-reported function. Materials and Methods: Eighty-four LBP patients were evaluated at baseline and after completion of a 6-week training program. Function was assessed with the modified Oswestry Disability Index (ODI) while TME was estimated using three tests: 1) the Biering-Sørensen, 2) the side bridge endurance tests (both sides), and 3) the trunk flexor endurance test. The standardized response mean (SRM) and the minimal clinical important difference (MCID) for each TME-test, and the relationships between changes in TME and improvement in ODI were calculated. Results: SRMs were small to large for TME-tests (range: 0.43 - 0.82), and large for the ODI (2.85) and no clinically useful MCID was identified for the TME-tests (area under the curve below 0.70). No significant correlations were found between changes in the TME and change in ODI scores (r < 0.15; all p > 0.05). Conclusion: Our results show a weak responsiveness of TME-tests in patients with LBP. There was no association between endurance performance change and self-reported functional change. TME-tests may not be a key component of rehabilitation monitoring in patients with LBP.